A Comprehensive 2022 Look at the Empirical Performance of Equity Premium Prediction - Goyal, Amit; Welch, Ivo; Zafirov, Athanasse (Review of Financial Studies, 2024)
Abstract Our paper reexamines whether 29 variables from 26 papers published after Goyal and Welch 2008, as well as the original 17 variables, were useful in predicting the equity premium in-sample and out-of-sample as of the end of 2021. Our samples include the original periods in which these variables were identified, but end later. More than one-third of these new variables no longer have empirical significance even in-sample. Of those that do, half have poor out-of-sample performance. A small number of variables still perform reasonably well both in-sample and out-of-sample.